1996
DOI: 10.1103/physrevlett.76.2790
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Glass and Lattice Melting Transitions in a YNi2B2C Singl

Abstract: The mixed state of the weakly disordered superconductor YNi 2 B 2 C is found to be similar to that of high-T c materials due to its large fluctuations. The very sharp resistive transition with a kink and the S-shaped I-V curve appear below H 1 T indicating a lattice melting transition. The scaling behavior of the vortex glass transition in R-T and I-V curves for H $ 2 T is observed with critical exponents n 1.23 6 0.02 and z 5.46 6 0.32, which are field independent. The vortex solid state changes from the vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
19
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 22 publications
6
19
0
Order By: Relevance
“…According to this vortex-glass ͑VG͒ theory, 21 the vortexglass correlation length ͑͒ diverges near T g , described by ϳ͉T − T g ͉ − and a correlation time scale z , where is a static exponent and z is a dynamic exponent. The experimental evidence for a vortex-glass phase has been identified for various superconductors such as YBa 2 Cu 3 O 7 , 22 YNi 2 B 2 C, 23 and MgB 2 ͑Ref. 24͒ through the scaling exponents and z in the range of ϳ 1-2 and z Ͼ 4, as predicted by the VG theory.…”
Section: Introductionmentioning
confidence: 98%
“…According to this vortex-glass ͑VG͒ theory, 21 the vortexglass correlation length ͑͒ diverges near T g , described by ϳ͉T − T g ͉ − and a correlation time scale z , where is a static exponent and z is a dynamic exponent. The experimental evidence for a vortex-glass phase has been identified for various superconductors such as YBa 2 Cu 3 O 7 , 22 YNi 2 B 2 C, 23 and MgB 2 ͑Ref. 24͒ through the scaling exponents and z in the range of ϳ 1-2 and z Ͼ 4, as predicted by the VG theory.…”
Section: Introductionmentioning
confidence: 98%
“…In the rare-earth nickel borocarbides RNi 2 B 2 C (R = Y, Dy, Ho, Er, Tm, Lu), the coherence lengths (ξ ∼ = 10 2Å ) and superconducting transition temperatures (16.1 K for R = Lu) lie between these extremes, suggesting that the vortex melting will be observable and may provide further information on vortex dynamics. Indeed, Mun et al 5 reported the observation of vortex melting in YNi 2 B 2 C, based on a sharp, kink-like drop in electrical resistivity.Recently, a magnetic field-driven FLL transition has been observed in the tetragonal borocarbides. 6,7,8,9 The transition from square to hexagonal vortex lattice occurs due to the competition between sources of anisotropy and vortex-vortex interactions.…”
mentioning
confidence: 99%
“…In the rare-earth nickel borocarbides RNi 2 B 2 C (R = Y, Dy, Ho, Er, Tm, Lu), the coherence lengths (ξ ∼ = 10 2Å ) and superconducting transition temperatures (16.1 K for R = Lu) lie between these extremes, suggesting that the vortex melting will be observable and may provide further information on vortex dynamics. Indeed, Mun et al 5 reported the observation of vortex melting in YNi 2 B 2 C, based on a sharp, kink-like drop in electrical resistivity.…”
mentioning
confidence: 99%
“…Moreover, when the vortex number N v is less than 50 corresponding to magnetic field below 0.025 T, we find the simulation result of YBa 2 Cu 3 O 7 shows a twist feature in the superconducting transition and an S-shaped current-voltage characteristic, which is a symbol of the first order lattice melting transition and also discovered in clean high-temperature samples [26,27].…”
Section: Simulation Resultsmentioning
confidence: 90%